The Implementation of the BTQ Program to Improve Quran Reading Skills of Students at SD Negeri 11 Sabang - Azmi, Nur; Suyanta, Sri; Maysa, Saifullah (Teunuleh Publisher, 2024)
The Al-Qur'an Reading and Writing Program (BTQ) aims to improve students' Qur'an reading skills according to Tajwid rules and foster religious character through systematic education. This study examines the planning, implementation, and assessment of the BTQ program at SD Negeri 11 Sabang using a descriptive qualitative approach. Data collection techniques included interviews, observations, and documentation. Findings reveal that program planning was thorough and structured, starting with initial assessments to gauge student abilities, curriculum development aligned with the school's vision, and scheduling that did not disrupt other lessons. The program involved key stakeholders such as the principal, vice principal, PAI teachers, and parents, ensuring comprehensive support. Implementation was student-centered, employing methods like iqra' and tahsin to enhance reading accuracy and Tajwid mastery, while also promoting religious character through motivational activities like Qur'an reading competitions. Collaboration with parents and material adjustments based on students’ abilities contributed to the program's smooth execution. Regular monitoring through assessments and classroom observations measured students' progress. Personalized support was provided for those needing extra assistance. With consistent monitoring and targeted guidance, the BTQ program effectively improved students' Qur'an reading skills and strengthened their religious character.